Validation of parameters and design of information system on the underground mining job safety with taking into account geomechanical factors - Shevchenko, V.G.; Slashchov, A.I. (Геотехнічна механіка, 2016)
This article is devoted to solution of one of the live scientific tasks: to determine regularities of dangerous geomechanical process occurrence and criteria for assessing risk of their development in the "support-rocks" system, and to validate parameters for the information system which could provide prompt making of decisions on ensuring safety of underground mining jobs with the help of current technologies: network communication, visual control and electronic documenting of data, which are of great importance for the job safety at the mining enterprises. On the basis of mathematical modeling methods, different scenarios of geomechanical process development around the roadways were assessed. The methods and rational parameters were developed for the information system elements functioning on ensuring the underground job safety. An architecture with the validated rational parameters was designed for the information system of the underground job safety, which differs by its methods for prompt predicting and assessing of different scenarios of geomechanical process development, and which includes the following subsystems: a basic client-server subsystem with functions of interaction between the personnel and management of the enterprise; a reference and information subsystem, which supports a decision making process, accumulates data and analyzes technical documentation; a subsystem for analyzing the job safety by geomechanical factors and for assessing of the "support-rocks" system state basing on the risk criteria and mathematical fuzzy logics. The job safety is improved thanks to the better interaction between the people and their more strict disciplinary responsibility and early decision-making on maintaining the roadways in the trouble-free state. Methodical recommendations were developed on how to use the information system for ensuring the underground job safety with taking into account geomechanical conditions of the rock mass. The recommendations, which include the information system functioning, preparation and deploy ment, and specificity of its application in different mining enterprises, were successfully approved and implemented.